Paranita, a new genus of spiders from northeastern Argentina (Araneae, Trachelidae): Phylogenetic datasets for phylogenetic analyses, and phylogenetic trees - Ramirez, Martin Javier (2023)
Alignments of 6 DNA markers and morphological data for the phylogenetic analysis of teh genus Paranita. For the phylogenetic analysis, we composed a dataset combining eight traditional target markers from the analysis of Wheeler et al. (2017) (12s, 16s, 18s, 28s, co1, H3), plus sequences from other sources and new co1 sequences for P. paulae (BOLD CORAR075, GenBank OR515542, MACN-Ar 30271) and Trachelopachys sericeus (BOLD SPDAR1264-15, GenBank OR515543, MACN-Ar 34546). Some markers were retrieved as bycatch from Sequence Read Archive (SRA) phylogenomic sequences (see publication for details). We used the morphological data accumulated in the datasets of Azevedo et al. (2022a) and Ramírez (2014). The analyses under maximum likelihood were made with IQ-TREE 2.2.0 (Minh et al. 2020). Models for each target-gene were selected by Bayesian information criterion with ModelFinder (Kalyaanamoorthy et al. 2017). The models selected for the sequence data were as follows: TIM2+F+G4 (12s and 16s), TNe+R2 (18s, co1-2, h3-1, h3-2), GTR+F+I+G4 (28s), GTR+F+I+G4 (co1-1), GTR+F+I+G4 (co1-3), GTR+F+I+G4 (h3-3). The morphological data was partitioned into two datasets, one with the unordered characters, another with the ordered ones, and analyzed with the Mk and Mk-ordered models, respectively, both with correction for ascertainment bias for the absence of invariant characters. Prior to analysis, all invariant characters were removed, and polymorphic entries were replaced by missing entries. The branch support was estimated with 1000 rounds of ultrafast bootstrap (Hoang et al., 2018). The analyses under maximum parsimony were made with TNT v 1.6 (Goloboff & Catalano, 2016) under equal weights using an exact search of implicit enumeration. Branch support was measured with 1000 rounds of jackknifing, representing frequencies over the optimal tree. See publication for references and details.